The Effect Of Progressive Muscle Relaxation On Nurse's Anxiety Level During Covid-19 Pandemic - Nurul Fatimah Bakri; Nurlina; Hariyanti Haris; Asri (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
The COVID-19 virus has become a worldwide pandemic. Nurses who work on the front lines to treat patients due to the COVID-19 outbreak may be exposed to the virus. This can certainly make nurses have more workloads and will be vulnerable to experiencing psychological problems in the form of anxiety. One of the non-pharmacological actions that can be taken to reduce anxiety is by doing progressive muscle relaxation because progressive relaxation techniques can focus on a muscle activity by identifying tense muscles and then reducing tension by doing relaxation techniques to get a relaxed feeling. Knowing the effect of progressive muscle relaxation on the anxiety level of nurses during the covid-19 pandemic in the emergency room and jasmine at H.A.Sultan Hospital Dg.Radja of Bulukumba. Methods This research uses a pre-experimental design using a one-group pre-post design. The sample of this study was 31 respondents who were taken by the Simple Random Sampling method. The DASS 42 questionnaire was used to assess the level of anxiety. Data analysis in this study used the T one sample statistical test. The results of the analysis used a one-sample T-test with a level of confidence (α = 0.05). Based on the results of this test, the p-value is 0.000, thus p < (0.000 < 0.05), then Ho is rejected and Ha is accepted. The conclusion of this study is that there is an effect of progressive muscle relaxation therapy on anxiety levels in nurses during the covid-19 pandemic in the emergency room and jasmine at H.A.Sultan Hospital dg. Radja Bulukumba and it is hoped that nurses will always be able to overcome the anxiety they experience.